Predation attempt by domestic cats (Felis catus) on a rondon’s marmoset (Mico rondoni) infant in an urban forest reserve in Porto Velho, Rondônia, Brazil - Oliveira, Marcela Alvares; Fernandes, Marcos (Neotropical Primates, 2021)
No abstract